Componentes agronômicos e índices fisiológicos da mandioca correlacionados ao preparo do solo - Figueiredo, Priscila Gonzales [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study aimed to evaluate the correlation between the physical characteristics of the soil, promoted by different tillage, and the qualitative and quantitative agronomic traits and physiologic indexes of cassava pla nt and identify at what time of plant development these correlations imply in possible differences in agronomic components. A field experiment was carried out in a randomized block split plot design with six replications. The types of tillage (minimum till age, conventional tillage and no tillage) were considered main plots and the times of evaluation, the subplots. The results, except for physiological indexes, were subjected to analysis of variance at 5% level of probability by F test, the treatments were compared by t test at 5% probability and times of evaluation were compared by regression. Additionally, all parameters were correlated by the Pearson coefficient. It was observed that the greater resistance to soil penetration in no tillage was a factor th at determined the larger partition of dry matter in the shoot rather than the roots ; in this treatment, the productivity of dry matter in the roots, at 210, 300, 330 and 360 days after planting (DAP), was about 2000 kg ha - 1 lower than for the other types o f tillage. It was concluded that the soil 's physical characteristics correlate with the qualitative and quantitative agronomic characters and do not correlate with the physiological ind exe s. These correlations imply qualitative differences from 120 DAP and quantitative differences from 150 DAP, and that macroporosity, total porosity and penetration resistance correlate directly with the productivity of dry mass of shoots...

O presente trabalho teve por objetivo avaliar as correlações entre as características físicas do solo, promovidas por diferentes tipos de preparo, os componentes agronômicos qualitativos e quantitativos e os índices fisiológicos da planta de mandioca e ide ntificar , em que época de desenvolvimento da planta , estas correlações implicam em possíveis diferenças na produtividade de raízes . F oi conduzido um experimento a campo em delineamento experimental de blocos ao acaso com parcelas subdivididas e seis repeti ções. O s preparos do solo (cultivo mínimo, CM; plantio convencional, PC e plantio sem revolvimento do solo, PSR) foram considerados parcelas e as épocas de avaliação as subparcelas . Os resultados, com exceção a os índices fisiológicos, foram submetidos à an álise de variância a 5% de probabilidade de erro pelo teste F, sendo os tratamentos comparados pelo teste de t a 5% de probabilidade e as épocas de avaliação por regressão. Adicionalmente, todos o s parâmetros foram correlacionad o s pelo do coefici ente de co rrelação de Pearson. Observou - se que a maior resistência a penetração do solo,observada no PSR foi um fator que determinou a maior partição de massa de matéria seca na parte aérea em detrimento às raízes. Neste tratamento, a produtividade de massa de maté ria seca nas raízes, aos 210, 300, 330 e 360 DAP foi cerca de 2000 kg ha - 1 inferior aos demais preparos do solo. Concluiu - se que a s características físicas do solo se correlacionam com os componentes agronômicos qualitativos e quantitativos e não se correl acionam com os índices fisiológicos. Estas correlações implicam em diferenças qualitativas a partir de 120 DAP e em diferenças quantitativas ...
Keywords: Mandioca - Fisiologia; Anatomia vegetal; Solos - Preparo; Solo adequado para agricultura; Cassava industry